Central vacancy creation in icosahedral nanoparticles induced by the displacement of large impurities - Nelli, Diana (European physical journal. Applied physics, 2022)
We employ metadynamics simulations at room temperature to study the diffusion of large single-atom impurities within otherwise pure icosahedral nanoparticles, for different bimetallic systems (Au-Co, Ag-Co, Ag-Ni, Au-Pt and Au-Rh) and icosahedral sizes. Our simulations reveal that the displacement of the impurity induces the formation of a vacancy in the central part of the structure, as already observed for small icosahedra of Au-Co and Ag-Cu, therefore confirming the generality of this peculiar diffusion process. At the largest size, a new collective displacement mechanism is identified alongside the diffusion of the impurity. For Au-Pt clusters, different diffusion pathways are observed, which are mediated by a partial deformation of the nanoparticle surface. This is due to the lack of stability of fivefold veritices in Pt icosahedral clusters. We prove that the stability of the icosahedral surface is an essential condition for the occurrence of the combined process of impurity diffusion and internal vacancy formation.